1998
DOI: 10.1063/1.366929
|View full text |Cite
|
Sign up to set email alerts
|

Growth of aluminum nitride on (111) silicon: Microstructure and interface structure

Abstract: The growth of hexagonal aluminum nitride directly on (111) silicon has been studied by grazing incidence x-ray diffraction and high resolution electron microscopy as a function of film thickness. Two epitaxial relationships were observed: (1) AlN (0001) [211¯0]//Si(111) [022̄], which prevails at deposition temperatures larger than 650 °C, and (2) AlN (0001) [101̄0]//Si(111) [022̄]. For a 40 Å thick layer, the average in-plane crystallite size is 162 Å, the in-plane rotation is ∼2° and the dislocations induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 15 publications
3
71
0
5
Order By: Relevance
“…The dislocations may create mosaic structure. (4) Successful growth of GaN epi-layer requires controlled nitridation of the Si surface and the growth of AlN buffer having small size of grains of about 20 nm. (5) Small GaN grains of about 20-nm size, relatively highly misoriented with respect to the c-plane, lead to the creation mosaic structure of the thick GaN layer grown on the Si(111) substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dislocations may create mosaic structure. (4) Successful growth of GaN epi-layer requires controlled nitridation of the Si surface and the growth of AlN buffer having small size of grains of about 20 nm. (5) Small GaN grains of about 20-nm size, relatively highly misoriented with respect to the c-plane, lead to the creation mosaic structure of the thick GaN layer grown on the Si(111) substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Heteroepitaxial GaN layers have been grown on many foreign substrates such as sapphire [1], silicon carbide [2] or silicon [3][4][5] for both optoelectronic and electronic applications. The success of the MOVPE epitaxy was discussed over many years, but the microscopic mechanism of the growth of low temperature buffer layer, and subsequent annealing and high temperature epitaxy is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to recent progress in identifying surface structural arrangements on GaN [1], there is only limited knowledge currently on the surfaces structures of AlN. Several studies have previously reported the symmetry of AlN surface reconstructions as seen by reflection high energy electron diffraction (RHEED) [2][3][4][5][6][7][8][9]. RHEED patterns with symmetries of 1×1 and 2×2 are commonly reported, a 2×6 pattern is also commonly seen, and a sequence consisting of 1×3, 3×3, and 6×6 is reported by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…Por ello, se hace necesaria la utilización de capas amortiguadoras que mejoren la calidad cristalina de la posterior epitaxia de GaN (2) . Por otra parte en el sistema que nos ocupa resulta fundamental el uso de capas amortiguadoras debido a que en el crecimiento de GaN directamente sobre Si se produce la formación de una capa amorfa en la intercara (3,4) , dificultando el crecimiento de epitaxias de nitruros con calidad suficiente para la fabricación posterior de dispositivos.En el presente trabajo se analiza la influencia del dopado con Si sobre la calidad estructural de heteroepitaxias GaN/AlN/ Si(111) mediante microscopía electrónica de transmisión y se estudian los mecanismos responsables de los cambios estructurales que tienen lugar en tales sistemas. …”
unclassified